A review on the negative impact of different elements during cyanidation of gold and silver from refractory ores and strategies to optimize the leaching process - Larrabure, G. (2021)
This research was supported by the Phosagro/UNESCO/IUPAC Partnership in Green Chemistry for Life (Contract ). JCFRR acknowledges the support of 4500245048FONDECYT and the World Bank (Contract 106-2018).The participation of GL was possible through the Real Life Experience (RLE) program at UTEC. Karinna Visurraga is thanked for administrative support.